REPRODUKTIVNI IZAZOVI ENDOMETRIJALNIH POLIPA: UTICAJ MATERNALNE STAROSTI I POVEZANIH RIZIČNIH FAKTORA - Milić, Sanja (Medical Research, 2025)
Introduction / Aim: Endometrial polyps (EPs) are abnormal growths that originate from the endometrium. Risk factors associated with EPs are hormonal changes related to ageing, Tamoxifen use, hormone replacement therapy (HRT), overweight or obesity. The exact causal relationship between EPs and infertility remains unclear, but multiple mechanisms including mechanical obstruction and biochemical changes are proposed. The “gold standard” for diagnosing and treatment EPs is hysteroscopy. The aim of this study is to correlate advanced maternal age with associated risk factors impact for EP in women dealing with infertility. Material and methods: Our study included 301 women undergoing hysteroscopic polypectomy due to infertility treatment, which were divided into two groups based on their age (age≤35 and age>35).  Data were collected from patients medical histories and pathology reports. Study variables included infertility type, T2DM, insulin resistance, PCOS, endometriosis, hypothyreosis, previous unsuccessful IUI and IVF, menstrual cycle irregularities and abnormal uterine bleeding (AUB), polyp size and histopathology type. Results: Previous history of unsuccessful IVF cycles was associated with older age (B = 1.703; p
Keywords: endometrial poyps, infertility, hysteroscopy